Design of pyrazolo-pyrimidines as 11β-HSD1 inhibitors through optimisation of molecular electrostatic potential1. Issue 5 (13th May 2015) - Robb, Graeme R.; Boyd, Scott; Davies, Christopher D.; Dossetter, Alexander G.; Goldberg, Frederick W.; Kemmitt, Paul D.; Scott, James S.; Swales, John G.
<x xml:space="preserve">Abstract</x> Rapid and efficient lead optimisation through quantification of the molecular electrostatic potential using quantum mechanics.